Design and characterisation of a high energy-density inductor - Saeed, Rasha (2018)
Power electronics is an enabler for the low-carbon economy, delivering flexible and efficient control and conversion of electrical energy in support of renewable energy technologies, transport electrification and smart grids. Reduced costs, increased efficiency and high power densities are the main drivers for future power electronic systems, demanding innovation in materials, component technologies, converter architectures and control. Power electronic systems utilise semiconductor switches and energy storage devices, such as capacitors and inductors to realise their primary function of energy conversion. Presently, roughly 50% of the volume of a typical power electronic converter is taken up by the energy storage components, so reducing their weight and volume can help to reduce overall costs and increase power densities. In addition, the energy storage densities of inductors are typically much lower than those of capacitors, providing a compelling incentive to investigate techniques for improvement. The main goal of this research was to improve the design of an inductor in order to achieve higher energy densities by combining significantly increased current densities in the inductor windings with the ability to limit the temperature increase of the inductor through a highly effective cooling system. Through careful optimisation of the magnetic, electrical and thermal design a current density of 46 A/mm2 was shown to be sustainable, yielding an energy storage density of 0.537 J/ kg. A principal target for this enhanced inductor technology was to achieve a high enough energy density to enable it to be readily integrated within a power module and so take a step towards a fully-integrated “converter in package” concept. The research included the influence of the operating dc current, current ripple, airgap location and operating frequency on the inductor design and its resulting characteristics. High frequency analysis was performed using an improved equivalent circuit, allowing the physical structure of the inductor to be directly related to the circuit parameters. These studies were validated by detailed small-signal ac measurements. The large signal characteristics of the inductor were determined under conditions of triangular, high-frequency current as a function of frequency, current (flux) ripple amplitude and dc bias current (flux) and a model developed allowing the inductor losses to be predicted under typical power electronic operating conditions.